Crime and Citizen security in Latin America. The Challenges for New Scholarship. - Bergman, Marcelo S. (Austin, Texas US: University of Texas Press)
Analiza el aumento de la criminalidad en América Latina, así como el descenso de la seguridad ciudadana.
Keywords: AMERICA LATINA; CRIMINILIDAD; SEGURIDAD